Human predatory behavior and the social implications of communal hunting based on evidence from the TD10.2 bison bone bed at Gran Dolina (Atapuerca, Spain). Issue 105 (April 2017) - Rodríguez-Hidalgo, Antonio; Saladié, Palmira; Ollé, Andreu; Arsuaga, Juan Luis; Bermúdez de Castro, José María; Carbonell, Eudald
Abstract: Zooarcheological research is an important tool in reconstructing subsistence, as well as for inferring relevant aspects regarding social behavior in the past. The organization of hunting parties, forms of predation (number and rate of animals slaughtered), and the technology used (tactics and tools) must be taken into account in the identification and classification of hunting methods in prehistory. The archeological recognition of communal hunting reflects an interest in evolutionary terms and their inherent implications for anticipatory capacities, social complexity, and the development of cognitive tools, such as articulated language. Late and Middle Paleolithic faunal assemblages in Europe have produced convincing evidence of communal hunting of large ungulates allowing for the formation of hypotheses concerning the skills of Neanderthals anatomically modern humans as social predators. However, the emergence of this cooperative behavior is not currently understood. Here, faunal analysis, based on traditional/long-established zooarcheological methods, of nearly 25, 000 faunal remains from the "bison bone bed" layer of the TD10.2 sub-unit at Gran Dolina, Atapuerca (Spain) is presented. In addition, other datasets related to the archeo-stratigraphy, paleo-landscape, paleo-environmental proxies, lithic assemblage, and ethno-archeological information of communal hunting have been considered in order to adopt a holistic approach to an investigation of the subsistence strategies developed during deposition of the archeological remains. The results indicate a monospecific assemblage heavily dominated by axial bison elements. The abundance of anthropogenic modifications and the anatomical profile are in concordance with early primary access to carcasses and the development of systematic butchering focused on the exploitation of meat and fat for transportation of high-yield elements to somewhere out of the cave. Together with a catastrophic and seasonal mortality pattern, the results indicate the procurement of bison by communal hunting as early as circa 400 kyr. This suggests that the cognitive, social, and technological capabilities required for successful communal hunting were at least fully developed among the pre-Neanderthal paleodeme of Atapuerca during the Lower Paleolithic. Similarly, the early existence of mass communal hunting as a predation technique informs our understanding of the early emergence of predatory skills similar to those exhibited by modern communal hunters. Resumen: La zooarqueología es una importante herramienta para la reconstrucción de la subsistencia y también para inferir aspectos relevantes del comportamiento social en el pasado. En este trabajo presentamos el análisis faunístico del llamado "lecho de huesos de bisonte", contenido en la subunidad TD10.2 del yacimiento Gran Dolina (Atapuerca, España). La composición taxonómica y perfil anatómico indican un conjunto monoespecífico fuertemente dominado por elementos del esqueleto axial de bisonte ( Bison sp.). Las características y abundancia de las modificaciones antrópicas revelan un acceso primario e inmediato a las carcasas, así como el desarrollo de un procesado carnicero sistemático dirigido a la explotación de la carne y grasa, y a la preparación para el transporte de elementos de alto rendimiento hacia algún lugar fuera de la cavidad. Esas características unidas a un perfil de mortalidad catastrófico y estacional, sugieren la obtención de los bisontes mediante caza comunal. La frecuencia, localización e intensidad de las mordeduras de carnívoro en los restos indica un fuerte saqueo de las carcasas de bisonte una vez abandonadas éstas por los homininos en el yacimiento. La suma de decisiones antrópicas sobre el transporte y el posterior saqueo por carnívoros de los despojos abandonados resulta en un conjunto interpretado como lugar de matanza y procesamiento carnicero de bisontes carroñeados posteriormente por las fieras. Las analogías etnográficas, etnohistóricas y arqueológicas nos han permitido interpretar el "lecho de huesos de bisonte" como cazadero utilizado durante varios eventos estacionales de caza comunal en los que rebaños completos de bisontes fueron sacrificados para ser explotados intensamente por los homininos que ocuparon la cueva. El repetido uso estacional de un punto en el territorio para el desarrollo de tareas específicas muestra ciertas similitudes con el patrón logístico de gestión de los recursos. En el mismo sentido, la existencia temprana de la caza comunal como táctica depredatoria nos informa sobre la emergencia de habilidades cognitivas, tecnológicas y sociales similares a aquellas exhibidas por otros cazadores comunales modernos en un momento tan temprano como el Pleistoceno medio.